Pengaruh Kualitas Sistem, Kualitas Informasi, Kualitas Pelayanan pada Kepuasan Pengguna dan Dampaknya pada Manfaat Bersih (Penelitian terhadap Sistem Informasi Surveilans Penyakit Tidak Menular) - Ira Fitria Yuniarti; Novrikasari Novrikasari; Misnaniarti Misnaniarti (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: This study aims to examine the influence of system quality, information quality, and service quality of  the  Non-Communicable Disease Manager Program at Public Health of Palembang. This  study  will  also  investigate  the  effect  on  user satisfaction and its impact on net benefits for users of Non Communicable Disease Surveillance Information System. This study applies a modification of the information system success model from DeLone & McLeanMethods: The model is analyzed by modeling the Structural Equation Modeling (SEM) based on components or variants (component based) that are popular with Partial Least Square (PLS) using SmartPLS version 3.0. The  results  of  this  study  are  expected  to  be  adopted  as  input  and  consideration  in  developing, and improving the performance of the Non Communicable Disease Surveillance Information System. The research design used in this study is quantitative research. Respondents in this study were 65 Manager Program of 41Public Health at Palembang who were actively working. The questionnaire was distributed directly by researchers on Januari 2020Result: The results showed that there was no effect between system quality quality on the user satisfaciton of this system. However, there was a positive and significant effect between information quality, and service quality on the user satisfaction of the system and between the  user satisfaction  of  the  system on  net  benefits.Conclusion : The  implementation  of  this information system can be declared successful because there is a  positive  correlation  between variables.